Corporate social responsibility, firm value, and influential institutional ownership - Buchanan, Bonnie; Cao, Cathy Xuying; Chen, Chongyang (Journal of Corporate Finance, 2018)
We examine how Corporate Social Responsibility (CSR), jointly with influential institutional ownership (IO), affects firm value around the 2008 global financial crisis. We find that the effect of CSR on firm value varies with the level of influential institutional ownership and depends upon economic conditions. Using difference-in-difference methods, we show that compared with non-CSR firms, CSR firms have higher firm values before the financial crisis but experience more loss in firm value during the crisis. Our findings suggest that the overall CSR effect depends on the relative dominance of two effects: conflict-resolution and overinvestment effect. In addition, we apply triple difference analysis and show that the relation between CSR and firm value depends upon the level of influential institutional ownership. Specifically, before the crisis, CSR positively affects the value of low institutional ownership firms and the effect is significantly weaker for firms with higher influential IO. During the crisis, the CSR-firm value relation is positive for high institutional ownership firms, suggesting that overinvestment concerns dominate when the crisis occurs. However, such a positive IO effect is not significant for CSR firms with high rollover risks. Our results are supported by a series of robustness tests.